Resiliensi Mahasiswa dari Keluarga Petani Sengon dalam Menghadapi Gagal Panen Akibat Karhutla - Garinda, Bella Patricia; Dwiky Ryamizardin; Irene Tangkilisan; Osi Karina Saragih; Muhammad Zusanri Batubara; Saputra Adiwijaya (Universitas Cenderawasih, 2024)
This research examines the resilience of students from sengon farming families in Pulang Pisau Regency in facing crop failure due to forest and land fires (karhutla). Descriptive qualitative methods were used through interviews, observations and literature studies. The research results show that forest and land fires, which are often caused by burning land without permission, cause significant economic losses for sengon farmers and their families. Affected students adopted resilience strategies such as income diversification, utilization of scholarships, good financial management, and sustainable agricultural development. Social support from the government and local communities focuses on preventing forest and land fires, but direct economic support is still minimal. This research highlights the importance of strengthening capacity and education for sengon farming families and students to build resilience in facing forest and land fires. The resilience demonstrated by students and families of sengon farmers in Pulang Pisau District-through diversification of income sources, utilization of social networks, and small-scale agricultural innovations-indicates that strengthening social capital and adaptive capacity are key to maintaining welfare sustainability amid the ecological and economic crisis caused by forest and land fires.